ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN OBAT RESEP PASIEN PROGRAM RUJUK BALIK (PRB) BPJS DI APOTEK X - Amalia, Sulastri; Mardiana, Lina Aliyani; Gunarti, Neni Sri (Jurnal Buana Farma, 2024)
The increase in the number of patients with chronic diseases makes the Program Rujuk Balik (PRB) BPJS play an important role in ensuring the effectiveness of treatment through the availability of medications at designated pharmacies. This study aims to analyze consumer satisfaction levels regarding the quality of prescription drug services of the Program Rujuk Balik (PRB) BPJS at Pharmacy X. The research employs a quantitative descriptive method involving 164 respondents selected using purposive sampling technique. Data were obtained through a questionnaire measuring five dimensions of service quality : physical evidence, reliability, responsiveness, assurance, and empathy. The results show that the level of consumer satisfaction with prescription drug services at Pharmacy X falls into the good category with an average score of 4.37. The level of satisfaction expected by consumers has an average score of 4.46, resulting in a gap value of -0.09, indicating that the service has met most of the consumers' expectations. In conclusion, the quality of prescription drug services under the Program Rujuk Balik (PRB) BPJS at Pharmacy X is rated as good, but there is still room for improvement, especially in aspects that show service gaps.